(untitled) (Revista de Artes Marciales Asiáticas, 2018)
The aim of this research was to identify versions of Mixed Martial Arts (MMA) as practiced in different settings. For this purpose, an ethnographic study was carried out in two MMA academies in the city of São Paulo, Brazil, during 2014. It was possible to identify these different versions through observations and conversations carried out during practices in these two settings. The research was based on theoretical approaches of Actor-Network Theory in dialogue with Constructionist Social Psychology. The results suggest that MMA is concomitantly a sport, a spectacle and an event within the logic of Economics. As such, it is multiple and cannot be reduced to a single, stable, predefined version given that each modality of practice can be translated into other distinct versions.